Changes in organic molecular marker signatures in soils amended with biochar during a three-year experiment with maize on a Fluvisol - Stefan Doerr (Journal of Hydrology and Hydromechanics, 2022)
Biochar is widely used as a soil amendment to improve soil properties and as a tool to absorb net carbon from the atmosphere. In this study we determined the signatures of organic molecular markers in soil following the incorporation of 5 and 10 t/ha biochar in a Fluvisol, cultivated with maize at the experimental field of the ISSAPP "N. Poushkarov"institute in Bulgaria. The n-alkane distribution in the biochar treated soils was uni- or bimodal maximizing at n-C17 alkane, n-C18 or C18 branched alkanes, i.e. there was an imprint of biomass burning, e.g. from the biochar due to predominance of short chain (< C20) homologues and increased microbial activity (presence of branched alkanes). This is also confirmed by the values for the average chain length (ACL) of n-alkanes which indicated prevalence of homologues of shorter chain (20-21 C atoms) in the variants of longer biochar residence time. There was evidence of trans-13-docosenamide, which originated from biochar. Fatty acids and fatty alcohols distributions also implicate microbial contribution to soil organic matter (SOM), supporting the suggestion that biochar addition can improve soil microbiological status.